PEMANFAATAN POC DAUN KELOR DAN AIR KELAPA UNTUK PENINGKATAN PERTUMBUHAN TANAMAN SAWI (Brassica chinensis L.) - Rian Arini; Waode Nuraida; Andi Awaluddin; Muhammad Safaruddin (Journal TABARO Agriculture Science, 2022)
Utilization of Moringa leaves as organic fertilizer is an easy, cheap and effective solution because of its enormous benefits in terms of the environment, agricultural / food security and socio-cultural sustainability. Mustard greens (Brassica chinensis L.) is a vegetable plant that is popular with the community, and has high economic value. This study aims to develop moringa leaves and coconut water which function as liquid organic fertilizer and growth regulators in increasing the growth of mustard plants. This research was conducted on his research was conducted at the Experimental Garden of the Faculty of Agriculture, Halu Oleo University, from October to November 2022, from October to November 2022. A total of 48 polybags of mustard plant seeds were maintained in 4 plots measuring 1x1x1 m with 1 plot containing 3 polybags for 21 days. The research design used was a randomized block design, consisting of 4 treatments with 4 replications in each experiment. The doses of liquid fertilizer for Moringa leaves and ZPT coconut water were P0 (0 ml/liter of water), P1 (150 ml/liter of water), P2 (200 ml/liter of water), and P3 (250 ml/liter of water). observed in this study included plant height, number of leaves, and leaf area. Observational data for each observed variable were analyzed based on variance. If there is a significant effect in the analysis of variance, then Duncan's multiple test (UJBD) is performed. From the results of statistical data analysis, it was found that the POC treatment of moringa leaves and coconut water had a very significant effect on plant height and leaf area, but had no significant effect on the number of leaves. These results indicate that there are differences in good plant growth. The best results on the growth of mustard plants were in the P3 treatment (250 ml/liter of water).